Surface-grafted polymer-assisted electroless deposition of metals for flexible and stretchable electronics - Liu, Xuqing; Zhou, Xuechang; Li, Yi; Zheng, Zijian (Chemistry, an Asian journal, 2012)
Surface-grafted polymers, that is, ultrathin layers of polymer coating covalently tethered to a surface, can serve as a particularly promising nanoplatform for electroless deposition (ELD) of metal thin films and patterned structures. Such polymers consist of a large number of well-defined binding sites for highly efficient and selective uptake of ELD catalysts. Moreover, the polymer chains provide flexible 3D network structures to trap the electrolessly deposited metal particles, leading to strong metal-substrate adhesion. In the past decade, surface-grafted polymers have been demonstrated as efficient nanoplatforms for fabricating durable and high-performance metal coatings by ELD on plastic substrates for applications in flexible and stretchable electronics. This focus review summarizes these recent advances, with a particular focus on applications in polymeric flexible and stretchable substrates. An outlook on the future challenges and opportunities in this field is given at the end of this paper.